Chemical surface modification of lithium disilicate needles of a silica-based ceramic after HF-etching and ultrasonic bath cleaning: Impact on the chemical bonding with silane. Issue 5 (May 2021) - Poulon-Quintin, A.; Ogden, E.; Large, A.; Vaudescal, M.; Labrugère, C.; Bartala, M.; Bertrand, C.
Highlights: Chemical surface modification of Lithium Disilicate ceramic after HF-Etching and ultrasonic bath cleaning. LiSi2 F6 nano-precipitates form on the Li2 Si2 O5 needles localized at the free surface of the Lithium Disilicate ceramic. Proposal of a mechanism to explain the impact on the chemical bonding with silane. Abstract: Objective: Recommendations to obtain the best bonding to silica-based ceramics are to prepare its surface by hydrofluoric-acid HF etching and regular application of a silane. This study investigated how the HF-etching following by ultrasonic water bath cleaning (recommended protocol to improve the bonding with a composite resin), modifies the surface chemistry of a lithium disilicate glass-ceramic and impacts the chemical bonding with silane. Methods: Lithium disilicate glass-ceramic discs (IPS Emax Press, Ivoclar Vivadent) were mirror polished, etched with 9% HF for 20 s and rinsed 1 min under water. Two post-etching cleaning were compared: (1) no additional cleaning and (2) immersion in water ultrasonic bath for 4 min. Morphology evolution of the surfaces was carried out by scanning electron microscopy. Chemical changes were studied using X-ray Photoelectron Spectroscopy and Nano Auger Electron Spectroscopy analyses. Identification of the compounds formed with fluorine was based on by High Resolution Transmission Tlectronic Microscopy . Results: Residues left on the surface of the discs after etching, the fluorine salts, were eliminated after the ultrasonic bath cleaning. However, analyses showed presence of fluorine on the lithium disilicate needles associated among others with the lithium. HR-TEM validates the presence of Li2 SiF6 crystallized phased. A mechanism to explain silane bonding when Li2 SiF6 phase is formed on the Li2 Si2 O5 needles, is proposed. Significance: HF-etching leads to the formation of lithium and fluorine contain LiSi2 F6 nano-precipitates on the Li2 Si2 O5 needles which helps to improve the bonding with silane.